Classification of Patients Visiting Online Patient Support Groups on Disease-Types on The Basis of Support Variables - Vivek Pandey (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study looks into how patients are grouped in Online Patient Support Groups based on the type of disease they have, using factors like homophily, perceived empathy, and perceived social support. The research explores how these factors differ among patients with rare, chronic, and life-threatening diseases. The data, collected from 700 participants between July 2020 and November 2022, were analyzed using discriminant analysis. The findings suggest that while there are noticeable but not strong differences in these factors among different diseases, patients with rare diseases tend to score higher. Despite the modest disparities, the analysis correctly identified disease types about 64.5% of the time, indicating that these factors can be helpful in identifying diseases among Online Patient Support Group users. However, more research is needed to fine-tune classification methods and account for the diversity within disease categories to enhance accuracy.